Comparison of different IRT-PAP protocols to screen newborns for cystic fibrosis in three central European populations - Sommerburg, Olaf; Krulisova, Veronika; Hammermann, Jutta; Lindner, Martin; Stahl, Mirjam; Muckenthaler, Martina; Kohlmueller, Dirk; Happich, Margit; Kulozik, Andreas E; Votava, Felix; Balascakova, Miroslava; Skalicka, Veronika; et al. (Journal of cystic fibrosis, 2014)
BACKGROUND: In recent years different IRT/PAP protocols have been evaluated, but the individual performance remains unclear. To optimize the IRT/PAP strategy we compared protocols from three regional CF newborn screening centers (Heidelberg, Dresden, and Prague). METHODS: We evaluated the effect of elevating the IRT-cut-off from 50 to 65 μg/l (~97.5th to ~99.0th percentile), the need of a failsafe protocol (FS, IRT ≥ 99.9th percentile) and the relative performance using either two IRT-dependent PAP-cut-offs or one PAP-cut-off. FINDINGS: Elevation of the IRT cut-off to 65 μg/l (~99.0th percentile) increased the PPV significantly (Dresden: 0.065 vs. 0.080, p < 0.0001, Prague: 0.052 vs. 0.074, p < 0.0001) without reducing sensitivity. All three IRT/PAP protocols showed a trend towards a higher sensitivity with FS than without and when using one PAP-cut-off instead of two IRT-dependent PAP-cut-offs. CONCLUSIONS: For best performance we suggest an IRT/PAP protocol with an IRT-cut-off close to the 99.0th percentile, FS, and a single PAP-cut-off.
Keywords: genetické testování; Cystic Fibrosis Transmembrane Conductance Regulator; Retrospective Studies; Europe; Evropa; Lectins, C-Type; Sensitivity and Specificity; novorozenecký screening; Trypsinogen; Prospective Studies; Chemistry, Clinical; lektiny typu C; Neonatal Screening; Cystic Fibrosis; Biomarkers, Tumor; Infant, Newborn; test suché kapky krve; novorozenec; nádorové biomarkery; protein CFTR; retrospektivní studie; prospektivní studie; Antigens, Neoplasm; Humans; klinická chemie; trypsinogen; senzitivita a specificita; Dried Blood Spot Testing; antigeny nádorové; Genetic Testing; lidé; cystická fibróza